How do autistic people fare in adult life and can we predict it from childhood?. Issue 2 (15th December 2022) - Forbes, Gordon; Kent, Rachel; Charman, Tony; Baird, Gillian; Pickles, Andrew; Simonoff, Emily
Abstract: This study describes social, mental health, and quality of life outcomes in early adulthood, and examines childhood predictors in the Special Needs and Autism Project (SNAP), a longitudinal population‐based cohort. Young autistic adults face variable but often substantial challenges across many areas of life. Prediction of outcomes is important to set expectations and could lead to the development of targeted early intervention. Autistic children were enrolled at age 12 and parents reported outcomes 11 years later when their children were age 23 ( n = 121). Thirty six percent of autistic adults were in competitive employment or education and 54% had frequent contact with friends. Only 5% of autistic adults were living independently, and 37% required overnight care. Moderate or severe anxiety and depression symptoms were found for 11% and 12% of young adults, respectively. Subjective quality of life was similar to UK averages except for social relationships. Using childhood IQ, autism traits and adaptive functioning meaningful predictions can be made of living situation, employment and education and physical health. Prediction was poor for friendships, mental health outcomes and other aspects of quality of life. Our results suggest that although young autistic adults face challenges across normative, social outcomes, they may be faring better in regard to mental health or quality of life. Childhood IQ, autism traits and adaptive functioning are most useful for predicting outcomes. After accounting for these factors, childhood measurements of behavioral and emotional problems and language offered little improvement in prediction of adult outcomes. Lay Summary: We asked parents of 121 autistic people questions about their children at age 12 and again, 11 years later in early adulthood. The autistic young adults faced challenges in employment and education, and many needed support for everyday living. We could make good predictions of these challenges using information from childhood. For other aspects of adult life, including mental health and quality of life, we could not make meaningful predictions of individual difficulties using the information we collected in childhood.